El docente itinerante de nivel inicial en la emergencia sanitaria por COVID 19 en la percepción de los padres de familia de la Institución Educativa Pública Inicial N° 279 Tamanco río Ucayali 2021 - Cisneros Sahuarico, Jessica (2022)
This section summarizes the findings found in the investigation, which is done taking into account the established objectives, the general objective was to determine the level of perception of the itinerant teacher of initial level in the health emergency by covid 19 in the parents of the Initial Public Educational Institution No. 279 of Tamanco Rio Ucayali in 2021. The type of descriptive research was considered, with a cross-sectional, univariate and field design. The study population was taken and shows 116 parents of the educational institution. The data was obtained through the survey as a technique and a questionnaire validated by expert judgment. It is concluded that the level of perception of the parents of the itinerant teacher of initial level in the health emergency by covid 19 in the Initial Public Educational Institution No. 279 of Tamanco, is medium at 11.2% while in the 88.8% have a high perception.